Theory of interface structure, energetics, and electronic properties of embedded Si/a-SiO2 nanocrystals - Hadjisavvas, George C.; Kelires, Pantelis C. (My University, 2007)
We examine the interrelation of the structural and bonding alterations, when Si nanocrystals are embedded in amorphous silicon dioxide, with the electronic properties of the resulting nanocomposite system. Monte Carlo simulations using a valence force-field model obtain the equilibrium structure of the interface, and investigate its energetics, stability and disorder as a function of the nanocrystal size. It is found that when the size is smaller than 2 nm, the embedded nanocrystals get heavily distorted. First-principles calculations of such small nanocrystals reveal a drastic reduction of the energy gap compared to the free-standing case. The origin of this pinning is attributed to the structural deformations, while oxygen states at the interface seem to play a minor role.
Keywords: Silicon nanocrystals; Silicon dioxide; Interface structure; Energetics; Electronic properties; Ab initio calculations